2015
DOI: 10.2147/ndt.s89916
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status, aggression, and poor driving distinguish traffic offenders from non-offenders but health status predicts driving behavior in both groups

Abstract: BackgroundIn Iran, traffic accidents and deaths from traffic accidents are among the highest in the world, and generally, driver behavior rather than technical failures or environmental conditions are responsible for traffic accidents. In a previous study, we showed that among young Iranian male traffic offenders, poor mental health status, along with aggression, predicted poor driving behavior. The aims of the present study were twofold, to determine whether this pattern could be replicated among non-traffic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Next, as regards mental health status, Possis et al 19 showed that, among veterans, risky driving behavior and poor mental health status were associated with poor driving behavior. Furthermore, in previous studies, 2 , 3 we have showed that, among both traffic offenders and non-offenders, poor mental health status was associated with both poor driving behavior and aggression, while aggression was also associated with poor driving behavior. However, when both poor health status and aggression were entered in a regression equation, only poor health status emerged as a predictor of poor driving behavior.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Next, as regards mental health status, Possis et al 19 showed that, among veterans, risky driving behavior and poor mental health status were associated with poor driving behavior. Furthermore, in previous studies, 2 , 3 we have showed that, among both traffic offenders and non-offenders, poor mental health status was associated with both poor driving behavior and aggression, while aggression was also associated with poor driving behavior. However, when both poor health status and aggression were entered in a regression equation, only poor health status emerged as a predictor of poor driving behavior.…”
Section: Introductionmentioning
confidence: 70%
“… 31 37 Third, we predicted that poor driving behavior would be independently predicted by poor sleep, poor general health, and higher aggression scores. 2 , 3 , 12 , 15 , 18 Fourth, we expected that poor sleep would predict poor driving behavior indirectly as well as directly. Finally, based on the studies by Schreier et al 42 and Hallvig et al, 43 we assumed that reaction time on a driving simulator as a proxy for objective driving behavior would not be related to subjective driving behavior or to psychological functioning (general health, subjective sleep, and aggression).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As described by Danaei et al [22], the infrastructure for primary health care and education has improved dramatically within the last two decades. Psychosocial, psychological and psychiatric interventions increased to help survivors of natural disasters or veterans with post-traumatic stress disorder (PTSD); to prevent unfavorable behavior such as suicidal ideation, domestic violence, and substance abuse; or to prevent unfavorable behavior related to traffic accidents [23][24][25]. On the flip side, there are still concerns about inadequacy of mental health services in Iran.…”
Section: Introductionmentioning
confidence: 99%